Knowledge Translation and Implementation Special Series. Implementing Treatment Frequency and Duration Guidelines in a Hospital-Based Pediatric Outpatient Setting: Administrative Case Report. - Hanson, Heather; Harrington, Ann Tokay; Nixon-Cave, Kim (Physical Therapy, 2015)
Background and Purpose. Determining treatment frequency and duration of physical therapist services is an important component of outpatient pediatric physical therapist practice, yet there is little research available to inform these decisions. Treatment frequency guidelines (TFG) can assist decision making in guiding pediatric physical therapy. The purpose of this project was to examine the feasibility and application of implementing TFG in hospital-based pediatric outpatient physical therapy. Project Description. Previously developed TFG were modified for use in our pediatric outpatient physical therapy department to include duration and were referred to as treatment frequency and duration guidelines (TFDG). In order to successfully implement the TFDG, there were 2 phases to the project. In phase 1, the staff were provided the guidelines and procedures in a staff meeting and via email using a PowerPoint presentation. Phase 2 was initiated due to the poor response of the staff in implementing the guidelines in their practice after phase 1. The format was changed to include formal re-education via small-group and one-on-one education sessions (phase 2). Chart reviews were completed to assess therapists' adherence to using TFDG. Outcomes. Therapists' adherence to use of TFDG increased following re-education: phase 1 (n=225 charts, 31% adherence) and phase 2 (n=197 charts, 90% adherence). Discussion. Treatment frequency and duration guidelines may assist in guiding frequency and duration decisions in pediatric physical therapy. Education via in-person meetings may improve adherence among staff.